Data mining and knowledge discovery handbook - Maimon, Oded; Rokach, Lior (New York : Springer, 2010)
Bacaan asas fakulti
Keywords: Data mining -- Handbooks, manuals, etc; Knowledge acquisition (Expert systems) -- Handbooks, manuals, etc